Caregiving and coping in carers of people with anorexia nervosa admitted for intensive hospital care1. Issue 4 (26th October 2012) - Raenker, Simone; Hibbs, Rebecca; Goddard, Elizabeth; Naumann, Ulrike; Arcelus, Jon; Ayton, Agnes; Bamford, Bryony; Boughton, Nicky; Connan, Frances; Goss, Ken; Lazlo, Bert; Morgan, John; et al.
Abstract Objective: The aim of the study was to examine how carers cope practically and emotionally with caring for individuals with anorexia nervosa who require intensive hospital care. Method: This study explores objective burden (time spent with caregiving and number of tasks), subjective burden (psychological distress), and social support in a sample of parents (n = 224) and partners (n = 28) from a consecutive series of patients (n = 178) admitted to inpatient units within the United Kingdom. Results: Most time was spent providing emotional support and less with practical tasks. Time spent with caregiving was associated with carer distress and was fully mediated by carer burden. This was ameliorated by social support. Partners received minimal support from others, and we found similar levels of burden and distress for mothers and partners. Discussion: The data indicate that professional and social support alleviates carer distress and may be of particular value for partners who are more isolated than parents. The data also suggest that time spent with practical support may be of more value than emotional support. © 2012 by Wiley Periodicals, Inc. (Int J Eat Disord 2013;)